System reliability analysis of bedrock-soil layer slopes subject to seismic action based on the upper bound limit analysis method - Qiangshan Yu; Yingbin Zhang; Dejian Li; Qiang Chen; Lirong Lin; Shihao Zhang; Wentao Jia (Geomatics, Natural Hazards & Risk)
Bedrock-soil layer slopes (BSLSs) are widely distributed in nature. The existence of the interface between bedrock and soil layer (IBSL) affects the failure modes of the BSLSs, and the seismic action makes the failure modes more complex. In order to accurately evaluate the safety and its corresponding main failure modes of BSLSs under seismic action, a system reliability method combined with the upper bound limit analysis method and Monte Carlo simulation (MCS) is proposed. Four types of failure modes and their corresponding factors of safety (Fs) were calculated by MATLAB program coding and validated with case in existing literature. The results show that overburden layer soil’s strength, the IBSL’s strength and geometric characteristic, and seismic action have significant effects on BSLSs’ system reliability, failure modes and failure ranges. In addition, as the cohesion of the inclination angle of the IBSL and the horizontal seismic action increase, the failure range of the BSLS gradually approaches the IBSL, which means that the damage range becomes larger. However, with the increase of overburden layer soil’s friction angle, IBSL’s depth and strength, and vertical seismic actions, the failure range gradually approaches the surface of the BSLS, which means that the failure range becomes smaller.